Nur dalam Perspektif Al-Ghazali - Khoirun Nisa'; Muhyidin (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2020)
Reading this character, it never ends. This figure who was born in the city of Thusi, has never escaped the study in the world of scientific studies. Namely Imam Ghozali. The type of research used in this research is library research, namely research carried out through collecting data or scientific writings aimed at the object of research or data collection that is library in nature, or studies carried out to solve a problem that is basically focused on on a critical and in-depth study of relevant library materials. As the 20th century Ghazalian Sulaiman Dunya once said about this figure” - in Tsaqafah Al-Ghazali - we will find in Imam Ghazali there are at least two madhabs; The "Lay" Madhab which has been summarized in Tahafut al-falasifah and the "Khawas" Madhab which has been followed by the philosophers3". Imam Al-Ghazali's discussion of Nur will be included in both, even Imam Ghazali wrote intensely and specifically about it in a small book called "Mishkat An-Anwar". The book which is considered complicated and full of formulas/symbols in the Sufi world by its reviewers, will explain a lot about the characteristics of Imam Ghazali's Sufism, especially regarding Nur (the light).